Peningkatan Literasi Kesehatan Digital Bagi Ibu-Ibu Rumah Tangga Di Posyandu Flamboyan, Bekasi - Rut Rismanta Silalahi; Puri Bestari Mardani; Maria Febiana Christanti (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Internet allows people to access various types of information, including health information. The problem is not all of the health information that circulating through Internet come from reliable sources. This community service intended to enhance the digital literacy on health information for the housewives in Flamboyan integrated healthcare center, Bekasi. Digital health literacy known as e-health literacy is the ability to seek, find, understand, and appraise health information from electronic sources and apply the knowledge gained to addressing or solving a health problem. These abilities are important especially for housewives since scientific research shows that there is a significant correlation between the levels of mother’s literacy and the health of family. Through this community service, the housewives in Flamboyan integrated healthcare center were trained to detect hoax through a simple fact-checking process. We found out that none of the participants know how to verify the health information that they get through social media or messaging application. They were only suspicious about the information that they get if the information contains title, content, or image that does not make sense. This community service has successfully shared the effective and simple way for housewives to do fact-checking process of health information with their own smartphones.